(untitled) (Scientific journal of the Fergana State University, 2023)
The article covers the concept of time and its specific interpretation, features of expression of temporality in world and Uzbek linguistics, importance of this concept in the example of Muhammad Yusuf’s poetry. The level of study of temporality in world and Uzbek linguistics, approaches to this phenomenon in philosophy and linguistics are described. The stages of the cognitive process, the perception and feeling of time through mental and emotional cognition, and detailed understanding in the development of language have been touched upon. The comprehensiveness, connection, manifestation of the concepts of space and time in the artistic text is highlighted. In Muhammad Yusuf’s poems, lexemes representing time are expressed at certain levels of the language. Language, as the main criterion in the formation of civilization, is developed and refined over time, analyzed on the example of Muhammad Yusuf’s poems. In linguistics, it is stated that the concept of time covers several areas at the same time.